2016
DOI: 10.1111/obr.12406
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis on the effects of exercise training versus hypocaloric diet: distinct effects on body weight and visceral adipose tissue

Abstract: Conflict of interest:All authors have no potential conflict of interest to report. Verheggen et al. 2 ABSTRACTExercise training ("exercise") and hypocaloric diet ("diet") are frequently prescribed for weight loss in obesity. Whilst body weight changes are commonly used to evaluate lifestyle interventions, visceral adiposity (VAT) is a more relevant and stronger predictor for morbidity and mortality. We performed a meta-analysis to assess the effects of exercise training or hypocaloric diet on VAT (quantified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
202
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(220 citation statements)
references
References 143 publications
10
202
4
4
Order By: Relevance
“…In the present study the estimation of visceral fat measured as an android region mass by DXA showed a substantial ~68% decrease followed by an increase back to the pre-values after the recovery period. A recent meta-analysis suggests that in negative energy balance, both exercise and diet reduce fat mass, but exercise may be more important to reduce visceral adipose tissue (Verheggen et al, 2016). The decrease in fat in these areas combined with energy deficit can, in theory, signal the hypothalamus-pituitary axis to decrease secretion of hormones relating to ovulation such as estradiol and eventually, to transiently stop ovulation and menstrual bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the estimation of visceral fat measured as an android region mass by DXA showed a substantial ~68% decrease followed by an increase back to the pre-values after the recovery period. A recent meta-analysis suggests that in negative energy balance, both exercise and diet reduce fat mass, but exercise may be more important to reduce visceral adipose tissue (Verheggen et al, 2016). The decrease in fat in these areas combined with energy deficit can, in theory, signal the hypothalamus-pituitary axis to decrease secretion of hormones relating to ovulation such as estradiol and eventually, to transiently stop ovulation and menstrual bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has recommended lifestyle interventions to reduce 5–10% of body weight as the primary preventive and management strategy for overweight and obesity 2. Excess fat mass, particularly in the visceral depot, results in more detrimental obesity-related health effects than just excess body weight 3. Reducing visceral adipose tissue improves cardiovascular and metabolic risk 4…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that weight loss is a poor marker for visceral adipose tissue change [21]. Whereas dietary restriction has superior effects on body weight reduction compared to exercise [22, 23], exercise tends to have superior effects in reducing visceral adipose tissue compared to caloric restriction [24]. The reduction of visceral adipose tissue is more important in the treatment of NAFLD than body weight loss.…”
Section: Discussionmentioning
confidence: 99%